Pediatric nephrology - Barratt, T. Martin; Avner, Ellis D; Harmon, William (Lippincott Williams and Wilkins, 1999)
Great Ormond Street Hospital for Children, London, UK. Comprehensive reference on renal function and disease in children. For clinicians in nephrology and pediatrics. This edition is shorter, lighter, and condensed. The senior author of the previous edition, c1994, was Malcolm A. Holliday. Halftone illustrations and numerous references. DNLM: Kidney Diseases--in infancy & childhood.
Keywords: nemoci ledvin; močové ústrojí; Child; nefrologie; Infant; dítě; pediatrie; kojenec; urologie; Urinary Tract; Kidney Diseases